2001
DOI: 10.1097/00005537-200110000-00004
|View full text |Cite
|
Sign up to set email alerts
|

5196 Mandible Fractures Among 4381 Active Duty Army Soldiers, 1980 to 1998

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. population data to all hospitalizations among active duty Army soldiers. Results: We found the following frequencies for specific mandible fracture locations: angle 35.6%, symphysis 20.1%, subcondylar 14.2%, body 12.7%, condylar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
2
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 11 publications
6
59
2
3
Order By: Relevance
“…In sixty patients (20.5%), there was occurrence of open fracture, whose data coincided with the world literature owing to the fact that mandible fractures are normally caused by major impact trauma (traffic accident, sport, firearm and others) 2,7,9 . Cranio-maxillo-facial and other system traumas have also been concomitantly detected, in agreement with the literature 15,17 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In sixty patients (20.5%), there was occurrence of open fracture, whose data coincided with the world literature owing to the fact that mandible fractures are normally caused by major impact trauma (traffic accident, sport, firearm and others) 2,7,9 . Cranio-maxillo-facial and other system traumas have also been concomitantly detected, in agreement with the literature 15,17 .…”
Section: Discussionsupporting
confidence: 92%
“…There are countries whose main cause of mandible fracture is related with sport activities, such as in Austria 16 . Others present interpersonal violence as the most common cause, such as Hawaii 17 , Zimbabwe 18 , Canada 19 . It is important to point out that there is predominance of occurrence of fracture at night hours and early Saturday and Sunday mornings, related with higher intake of alcoholic drinks 6,10 .…”
Section: Discussionmentioning
confidence: 99%
“…O principal fator etiológico das fraturas mandibulares observado nesta pesquisa foi o acidente com veículos automotores e coincidem com a grande maioria dos trabalhos pesquisados 1,3,6,7,10,[14][15][16] , seguidos de perto pelas agressões físicas que em outros estudos 3,[17][18][19] é o principal fator etiológico. O acidente esportivo foi a causa principal de fraturas mandibulares 20 .…”
Section: Leporace Leporace Leporace Leporaceunclassified
“…Boole et al (1) reported 5,196 mandibular fractures, of which only 30 (1%) involved the coronoid process. Dingman and Natvig (2) stated that 2% of fractures of the mandibular condyle occur in the region of the coronoid process.…”
Section: Introductionmentioning
confidence: 99%